2021
DOI: 10.4103/japtr.japtr_69_21
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of flavonoid from local plant Eriocaulon cinereum R.B against MCF-7 breast cancer cells

Abstract: Eriocaulon cinereum R. Br is used as traditional medicine by the local community in Bangka Belitung Island, Indonesia. The plant is processed as an infusion for fever, boosts the immune system, and treats tumor cells. However, scientific research on this species is still limited. The aims of this study were to determine the cytotoxic of E. cinereum against MCF-7 cells. The results suggested that one of the compounds has a good cytotoxic activity. Therefore, it is quite promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The active isolate that was successfully isolated from the fraction, which is a flavonoid isolate, has an IC50 of 7.28 μg/mL. [20][21][22] The same results were also found upon testing toxicity on T47D cells. The subfraction containing terpenoids had a lower IC50 compared to the dichloromethane fraction, with IC50 values of 84.8 and 131.921 μg/mL, respectively.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…The active isolate that was successfully isolated from the fraction, which is a flavonoid isolate, has an IC50 of 7.28 μg/mL. [20][21][22] The same results were also found upon testing toxicity on T47D cells. The subfraction containing terpenoids had a lower IC50 compared to the dichloromethane fraction, with IC50 values of 84.8 and 131.921 μg/mL, respectively.…”
supporting
confidence: 65%
“…These results follow previous studies of MCF-7 or T47D cells, in line with the hypothesis proposed in this study. [20][21][22][23][24][25][26] The compound selectivity index, which was also determined in this study, showed that the selectivity of compounds in normal Vero cells was 2.157, which is classified as being in a good category with a value >2. This shows that the compound is selective and can differentiate between cancer cells and normal cells.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Flavonoid compounds found in the plant Eriocaulon cinereum R.B. by phytochemical screening was reported to exhibit anticancer activity in MCF-7 cells with an IC50 of 7.28 ± 6.75 μg/mL [49]. According to Slika et al [50], flavonoid compounds have anticancer properties because they are able to eliminate reactive oxygen species (ROS), inhibit oxidase enzyme, chelate metals, and activate antioxidant enzymes.…”
Section: -6-anticancer Testmentioning
confidence: 99%